(untitled) (Revista do CEDS, 2022)
The purpose of this paper is to know the criteria used by companies when setting prices for products aimed at women, as well as how they are affected by price discrimination by gender. The article contains points of view, references, and studies from different authors, in order to verify the hypothesis that gender pricing is an act of discrimination against women.